Pengaruh Pelatihan IT Fundamental, Keterampilan, Dan Pengalaman Kerja Terhadap Produktivitas Kerja Karyawan (Studi Kasus Pengembangan SDM di Universitas Muslim Indonesia) - Nur Rahmadani; Mallongi, Syahrir; Arifin, Zaenal (Jurnal Online Manajemen ELPEI, 2024)
Research objectives: (1) Analyze the influence of fundamental IT training on employee work productivity on the Indonesian Muslim University campus (2) The influence of work skills on employee work productivity on the Indonesian Muslim University campus, (3) The influence of work experience on employee work productivity on the Muslim University campus Indonesia. The research method used is quantitative with a survey approach, where data is collected through questionnaires distributed to employees of the Indonesian Muslim University. The population used in this research was 200 employees who had taken Fundamental IT training and based on calculations from the Slovin formula, a sample of 67 respondents was obtained. Data analysis was carried out using multiple linear regression to identify how much influence each independent variable has on work productivity.                 The research results show that: (1) Fundamental IT training does not have a positive and significant influence on employee work productivity (2) Work Skills have a positive and significant influence on employee work productivity (3) Work Experience has a positive and significant influence on employee work productivity.